The phosphodiesterase-5-inhibitor udenafil lowers portal pressure in compensated preascitic liver cirrhosis: a dose-finding phase-II-study - Kreisel, Wolfgang; Deibert, Peter; Kupcinskas, Limas; Sumskiene, Jolanta; Appenrodt, Beate; Roth, Susanne; Neagu, Michaela; Rössle, Martin; Zipprich, Alexander; Caca, Karel; Ferlitsch, Arnulf; Dilger, Karin; et al. (Digestive and liver disease, 2015)
Liver cirrhosis, phosphodiesterase-5-inhibitors, portal hypertension, portal pressure, udenafil